2006
DOI: 10.1063/1.2216911
|View full text |Cite
|
Sign up to set email alerts
|

Optical luminescence from alkyl-passivated Si nanocrystals under vacuum ultraviolet excitation: Origin and temperature dependence of the blue and orange emissions

Abstract: The origin and stability of luminescence are critical issues for Si nanocrystals which are intended for use as biological probes. The optical luminescence of alkyl-monolayer-passivated silicon nanocrystals was studied under excitation with vacuum ultraviolet photons ͑5.1-23 eV͒. Blue and orange emission bands were observed simultaneously, but the blue band only appeared at low temperatures ͑Ͻ175 K͒ and with high excitation energies ͑Ͼ8.7 eV͒. At 8 K, the peak wavelengths of the emission bands were 430± 2 nm ͑b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
32
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 45 publications
8
32
1
Order By: Relevance
“…Sham et al [38] measured X-ray excited optical luminescence (XEOL) and X-ray emission spectroscopy (XES) on silicon nanowires and showed that the blue emission is associated with the silicon oxide layer on the samples. This suggests that the blue PL emission is from oxidized Si species and the red PL emission originates from unoxidized Si core, which is in agreement with the previous results from alkyl Si-QDs [26]. It should be noted that the PL colour will be dominated by the main peak 604 nm here, which is red.…”
Section: Photoluminescence Spectroscopysupporting
confidence: 91%
See 1 more Smart Citation
“…Sham et al [38] measured X-ray excited optical luminescence (XEOL) and X-ray emission spectroscopy (XES) on silicon nanowires and showed that the blue emission is associated with the silicon oxide layer on the samples. This suggests that the blue PL emission is from oxidized Si species and the red PL emission originates from unoxidized Si core, which is in agreement with the previous results from alkyl Si-QDs [26]. It should be noted that the PL colour will be dominated by the main peak 604 nm here, which is red.…”
Section: Photoluminescence Spectroscopysupporting
confidence: 91%
“…The motivation behind this work is twofold: over the course of exposure the QDs are observed to undergo a photon-induced oxidation, based on the evolution of the Si2p core level, and so is of interest from a purely investigative perspective in furthering our understanding of their luminescence behaviour. Similar photon-oxidation effects have been observed in light-emitting porous silicon [23], germanium nanocrystals [24], alkylated silicon nanocrystals [25,26], and crystalline silicon surfaces [27,28], where the photon source was either a laser, UV, EUV/VUV, or X-rays. This work is of particular value owing to the ability to disperse acrylic acid grafted Si-QDs in water which may offer new routes towards bio-imaging applications within living systems.…”
supporting
confidence: 55%
“…In order to investigate the detailed temperaturedependent behavior of Si NCs further, temperature quenching spectra were obtained by Chao et al [64] with 21 eV excitation energy as the temperature was increased at a rate of 15 K min À1 (Figure 10). The monochromator for the detector, a photomultiplier tube (PMT), was set at blue and orange wavelengths, 420 AE 10 nm (blue) and 610 AE 10 nm.…”
Section: Origin Of the Orange And Blue Pl Emissionmentioning
confidence: 99%
“…Higher-resolution images were obtained by STM on alkylated n-Si (111) substrates in which individual Si NCs could be resolved within the islands. If the source temperature was set to 200 C, the mean diameter of the Si cores was 1.8 AE 0.34 nm for the evaporated material compared to 2.2 AE 0.38 nm for as-prepared alkyl-Si NCs [12,64,71]. The ability to evaporate and deposit NCs in ultrahigh vacuum (UHV) should be useful for the size-controlled preparation of new nanoscale quantum-confined structures.…”
Section: Floating Gate In Memory Devicesmentioning
confidence: 99%
“…These are major factors which have helped drive interest in the synthesis and application of SiNPs over the past twenty years (Ahire et al, 2012, Wilson et al, 1993, Kang et al, 2011, Chao et al, 2007. Quantum confinement effects give SiNPs interesting optical, electronic and mechanical properties (Reboredo and Galli, 2005, Pavesi et al, 2000, Chao et al, 2006, O'Farrell et al, 2006, Rosso-Vasic et al, 2008.…”
Section: Introductionmentioning
confidence: 99%